2020
DOI: 10.5194/tc-2020-154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of small-scale snow surface roughness on snow albedo and reflectance

Abstract: Abstract. The primary goal of this paper is to present a model of snow surface albedo accounting for small-scale surface roughness effects. The model is based on photon recollision probability and it can be combined with existing bulk volume albedo models, such as TARTES. The model is fed with in situ measurements of surface roughness from plate profile and laser scanner data, and it is evaluated by comparing the computed albedos with observations. It provides closer results to empirical values than volume sca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…SNICAR also accounts for the incident radiation at the surface and its spectral distribution, solar zenith angle, snow depth and density, snow layer number, and the type and concentration of LAPs in the snowpack. The model's ability to provide realistic simulations of snow albedo has been verified by several previous studies (Hadley and Kirchstetter, 2012;Meinander et al, 2013;Zhong et al, 2017;Wang et al, 2017).…”
Section: Radiative-transfer Modelsupporting
confidence: 55%
“…SNICAR also accounts for the incident radiation at the surface and its spectral distribution, solar zenith angle, snow depth and density, snow layer number, and the type and concentration of LAPs in the snowpack. The model's ability to provide realistic simulations of snow albedo has been verified by several previous studies (Hadley and Kirchstetter, 2012;Meinander et al, 2013;Zhong et al, 2017;Wang et al, 2017).…”
Section: Radiative-transfer Modelsupporting
confidence: 55%
“…In this study, we performed one anisotropy correction in each MODIS pixel, while >200 anisotropy corrections were performed in each MODIS pixel extent for the L5/TM and L8/OLI albedo retrieval, and this effect can be more pronounced on complex and heterogeneous surfaces and lead to albedo difference [26]. Second, since surface topography and roughness can alter solar-surface-satellite geometry and irradiance very locally, Landsat instruments can capture these changes better than MODIS, which inevitably leads to albedo differences [53,[55][56][57]. However, unlike the validation of MCD43A3 in Greenland and large ice caps in Iceland, both our study and that of Pope et al [26] and Wang et al [24] showed that MODIS underestimated albedo on mountain glaciers.…”
Section: Evaluation Of the Albedo Productsmentioning
confidence: 99%